Notes on pollination ecology of Altensteinia fimbriata Kunth in the city of Quito, Ecuador - Martín Carrera; Luis Baquero (Journal of Pollination Ecology)
Most orchid species face significant challenges in urban environments. Particularly, pollination services and reproductive success can be altered due to habitat fragmentation related to human activities. Despite this, several terrestrial orchid species thrive in these environments. This study investigates the pollination ecology of Altensteinia fimbriata, a terrestrial orchid prevalent in disturbed habitats from the neotropics. This research aims to identify the pollination mechanism and to list the pollinators and floral visitors associated to A. fimbriata. During 30 hours of observation in a patch with 60 inflorescences of A. fimbriata within an anthropic area of the city of Quito, Ecuador, we recorded 121 visits from ten moth species, identifying four moth species as effective pollinators. Three of the pollinator species were noctuid moths. Moth activity peaked in the evening, coinciding with the emission of distinctive floral scents, suggesting that both scent and nectar attract visitors. We found that the four pollinators of A. fimbriata transfer pollinariums using their legs. This pollination mechanism is found in other terrestrial orchid species from different subtribes where noctuid moths are also the main pollinators. Our findings highlight the adaptability of A. fimbriata in urbanized areas and emphasize the need to understand its pollination dynamics in the context of global change.